Precise 1H- and 13C-NMR reassignment of dehydrocrebanine by 10-mg INADEQUATE and in silico analysis: With an alert for its toxicity. Issue 27 (3rd July 2020) - Phupong, Chotika; Suenaga, Masahiko; Bhoopong, Phuangthip; Chunglok, Warangkana; Jaritngam, Gunlanan; Karak, Milandip; Yoshida, Keiichi; Phupong, Worrapong; Torikai, Kohei
Abstract: During our continuous investigation on a Thai traditional medicinal plant, Stephania venosa Spreng, an alkaloid that seemed to be O -methyldehydrobulbocapnine (MDB) or dehydrocrebanine (DC), had been isolated. However, none of the previously reported 1 H- and 13 C-NMR data for MDB and DC matched our charts. Thus, we herein report the unambiguous determination of the alkaloid structure as DC via a successful INADEQUATE experiment using 10 mg of the unenriched natural specimen as well as an in silico estimation. Furthermore, our biological assay revealed that both the dichloromethane extract of S. venosa and the isolated DC show cytotoxicity to murine macrophage cells, which should be alerted to a folk doctor community that are using S. venosa to treat patients. Graphical abstract: Image 1 Highlights: A successful INADEQUATE NMR experiment, using 10 mg of unenriched natural specimen. An 800 MHz device with a liquid helium temperature probe enabled the INADEQUATE DFT-based chemical shift prediction giving insights for structure determination. Caution to a folk medicine community using S. venosa, having toxic ingredients.